Presynaptic regulation of the inhibitory transmission by GluR5-containing kainate receptors in spinal substantia gelatinosa - Pinaud Raphael; Jia Yongheng; Vadakkan Kunjumon I; Toyoda Hiroki; Zhao Ming-Gao; Wu Long-Jun; Xu Hui; Zhuo Min (Molecular Pain, 2006)
Abstract GluR5-containing kainate receptors (KARs) are known to be involved in nociceptive transmission. Our previous work has shown that the activation of presynaptic KARs regulates GABAergic and glycinergic synaptic transmission in cultured dorsal horn neurons. However, the role of GluR5-containing KARs in the modulation of inhibitory transmission in the spinal substantia gelatinosa (SG) in slices remains unknown. In the present study, pharmacological, electrophysiological and genetic methods were used to show that presynaptic GluR5 KARs are involved in the modulation of inhibitory transmission in the SG of spinal slices in vitro. The GluR5 selective agonist, ATPA, facilitated the frequency but not amplitude of spontaneous inhibitory postsynaptic currents (sIPSCs) in SG neurons. ATPA increased sIPSC frequency in all neurons with different firing patterns as delayed, tonic, initial and single spike patterns. The frequency of either GABAergic or glycinergic sIPSCs was significantly increased by ATPA. ATPA could also induce inward currents in all SG neurons recorded. The frequency, but not amplitude, of action potential-independent miniature IPSCs (mIPSCs) was also facilitated by ATPA in a concentration-dependent manner. However, the effect of ATPA on the frequency of either sIPSCs or mIPSCs was abolished in GluR5-/- mice. Deletion of the GluR5 subunit gene had no effect on the frequency or amplitude of mIPSCs in SG neurons. However, GluR5 antagonist LY293558 reversibly inhibited sIPSC and mIPSC frequencies in spinal SG neurons. Taken together, these results suggest that GluR5 KARs, which may be located at presynaptic terminals, contribute to the modulation of inhibitory transmission in the SG. GluR5-containing KARs are thus important for spinal sensory transmission/modulation in the spinal cord.